De Pamplona a Aviñón y París. Las cuentas de un viaje a mediados del siglo XIV (1355-1356) - Serrano Larráyoz, Fernando; Mugueta Moreno, Íñigo (Huarte de San Juan. Geografía e Historia, 2007)
There could be found some curious evidences in the Archivo General de Navarra. In this case it is a book of expense account done by Guillaume de Meaucourt, the Ribera’s receiver (Navarre) from 1355 to 1356, in a trip that took him from Pamplona to Avignon and Paris. Being Charles ii (“the Bad”), the navarresse king, in Paris, his brother Louis, who was the governor of the reign, sent him a messenger to report about many important questions of the government: Guillaume de Meaucourt. Due to the countable document this official drew up we are nueallowed to know the route, the food, and every expense on supplying during the journey from Pamplona to Paris. His task was to solve the problem about the succession in the bishopric after the last bishop died. In fact, Guillaume de Meaucourt´s trip took him first to Avignon where he had an interview with the Pope. The itinerary went over Navarre Aragon, Catalonia and a great part of France, so there were necessary many money exchanges for supplying. Our attention has been also focused on this important question.
Keywords: Trip; embassy; food; Navarre; Aragon; Catalonia; France; fourteenth [14th] century